Paradigma Konsep Teori dan Praktek Baitul Maal Dalam Prespektif Sistem Ekonomi Islam - Sumadi Sumadi; Muhammad Tho'in (ITB AAS INDONESIA Surakarta, 2020)
This study aims to rectify the understanding of the concept of baitul mal in the view of the Islamic economic system. This type of research is a qualitative research, and the short model in this study is a descriptive approach that uses the literature study method as the settlement methodology. With the object of a case study about straightening the concept of baitul mal in the view of the Islamic economic system. Baitul Mal comes from the Arabic bait which means house, and al-mal which means property. So etymologically (ma'na lughawi) Baitul Mal means a house to collect or store wealth (Dahlan, 1999). As for terminology (ma'na ishtilahi), as explained by Abdul Qadim Zallum (1983) in his book Al Amwaal Fi Daulah Al Khilafah, the Baitul Mal is an institution or party (Arabic: al jihat) which has a special duty to handle all the people's assets in the form of State revenue and expenditure. In the history of the Baitul Mal, especially with regard to the organizational structure and administration, the term Diwan is known. Diwan is a place where the authors / secretaries of the Baitul Mal are located and a place to store archives. The term Diwan is sometimes also used in the sense of the archives themselves, because there are indeed interrelations between the two meanings for this word Diwan. In summary, Diwan can mean the office of the Baitul Mal, or archive of the Baitul Mal.